Jungian psychotherapy with medical professionals : healing the healer - Hales, Suzanne (London : Routledge, 2022)
Jungian Psychotherapy with Medical Professionals guides therapists, clinicians, and healthcare workers through the transformative healing process of Jungian psychology, demonstrating how the new spirit of medicine will originate from the relationship between the healer and the healed. Through extensive experience and scientific research gathered over the past four decades working closely with physicians, Suzanne Hales presents the telling of their stories that have been historically hushed or hidden away. Hales offers a lifeline for healthcare workers as she weaves together the stories of physicians and their patients with gripping honesty, presenting an intimate glimpse of what happens in the lives of healers and the healed. The book offers support to the healer in need of healing, provides hope for wholeness and restoration, and advocates for those who spend their lifetime advocating for others. The book is of great interest to Jungian analysts, therapists, and trainees, and it is essential reading for anyone working in healthcare, including physicians and healers of all kinds in the landscape of modern medicine.
1: We Are Alone; 2: The Call; 3: Learning to Breathe Under Water; 4: When the Heart Freezes; 5: From Ashes to Archetypes; 8: The Reclamation of Needs; 7: The Problem of Eros and Logos in Medicine; 8: The Shadow Side of Medicine; 9: The Wounded Sexuality of Todayś Physician; 10: Suffering; 11: A Mythic Monster Named Shame; 12: Redeeming the Voice of the Physician Through Jungian Pathways; 13: The Offering
Includes index.
Keywords: Jungian psychology; Psychotherapy; Medical personnel -- Mental health; Medical personnel -- Counseling of; MEDICAL / Caregiving; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Movements / Jungian